Evidence Review of Topical Calcineurin Inhibitors for the Treatment of Adult Atopic Dermatitis. Issue 4 (September 2019) - Hong, Chih-ho; Gooderham, Melinda; Bissonnette, Robert
Topical calcineurin inhibitors (TCIs) were approved in the early 2000s for the treatment of atopic dermatitis (AD), and despite the recent introduction of newer topical and systemic therapies for AD, TCIs such as tacrolimus ointment (0.03% and 0.1%) and pimecrolimus cream (1%), remain recommended treatment options in contemporary management guidelines. The goal of this article is to review the evidence supporting the approved indications for TCIs in adults with AD, including short-term treatment of active disease and as intermittent or maintenance treatment for the prevention of flares. Other evidence reviewed in this article includes the treatment of specific body areas (such as the face and eyelids), combination or sequential use of TCIs with topical corticosteroids, and the comparative efficacy of the 2 commercially available TCIs. This review of the evidence confirms that TCIs remain an effective treatment option for the management of adult AD.